Peripheral CD4 + T cells mediate the destructive effects of maternal separation on prefrontal myelination and cognitive functions - Rui Xiong; Yinyin Hu; Menghan Wang; Ting Han; Yuying Hu; Chaolin Ma; Baoming Li (Proceedings of the National Academy of Sciences, 2025)
Maternal separation (MS), a chronic stress event in early life, impairs myelination in the prefrontal cortex (PFC) and leads to PFC cognitive disorders. It remains largely unclear how such deficits are mediated. Here, we show that peripheral CD4 + T cells play an essential role in mediating the destructive effects of MS on medial prefrontal cortical (mPFC) myelination and cognitive functions in mice. Offspring mice with MS experience (MS mice) exhibited an increase in CD4 + T cells and xanthine levels in peripheral blood and a severe deficit in mPFC-dependent cognitive functions such as working memory, social interaction, and anxiety/depression emotion regulation, along with a decrease in oligodendrocyte precursor cells (OPCs) and oligodendrocytes (OLs) in the mPFC. These phenotypes were rescued upon treatment with the antibody neutralizing peripheral CD4 + T cells. Rag1 −/− immunodeficient mice receiving transplantation of CD4 + T cells isolated from the peripheral blood of MS mice showed similar phenotypes as observed in MS mice. Immunofluorescence staining revealed a rich expression of adenosine receptor A1 (A1) in OPCs in the mPFC, and the A1-expressing OPCs decreased in the Rag1 −/− mice receiving CD4 + T cell transplantation. The present study demonstrates a causal link between peripheral CD4 + T cells and MS-induced prefrontal cortical hypomyelination and cognitive dysfunction, and such a link is probably mediated via xanthine–adenosine receptor A1 signaling in OPCs.